2019
DOI: 10.1101/560672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell q-PCR derived expression profiles of identified sensory neurons

Abstract: Sensory neurons are chemically and functionally heterogeneous and this heterogeneity has been examined extensively over the last several decades. These studies have employed a variety of different methodologies, including anatomical, electrophysiological and molecular approaches. Recent studies using next generation sequencing techniques have examined the transcriptome of single sensory neurons. Although, these reports have provided a wealth of exciting new information on the heterogeneity of sensory neurons, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Although our RNAseq data support an ECM-dependent mechanism in the alterations of PVI membrane properties, we acknowledge that the excitable properties of neurons, which can be influenced by localization or phosphorylation, may not always align to the transcriptomic level of a particular ion channel. Although RNA-Seq transcriptomic profiling provides a comprehensive analysis of actively regulated genes, many studies have found no correlation or seemingly inverse relationships between the expression of various membrane ( Adelman et al., 2019 ; Bomkamp et al., 2019 ; Földy et al., 2016 ; Larson et al., 2016 ; Tripathy et al., 2017 ) and synaptic ( Fazel Darbandi et al., 2018 ; Harrington et al., 2016 ; Yook et al., 2019 ) genes with their electrophysiological properties. Thus, the relationship between gene expression and cellular/behavioral phenotypes is complex, and this complexity must be taken into account in future studies into the ion channel mechanisms mediating hypoexcitability of PVIs in Arx CKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although our RNAseq data support an ECM-dependent mechanism in the alterations of PVI membrane properties, we acknowledge that the excitable properties of neurons, which can be influenced by localization or phosphorylation, may not always align to the transcriptomic level of a particular ion channel. Although RNA-Seq transcriptomic profiling provides a comprehensive analysis of actively regulated genes, many studies have found no correlation or seemingly inverse relationships between the expression of various membrane ( Adelman et al., 2019 ; Bomkamp et al., 2019 ; Földy et al., 2016 ; Larson et al., 2016 ; Tripathy et al., 2017 ) and synaptic ( Fazel Darbandi et al., 2018 ; Harrington et al., 2016 ; Yook et al., 2019 ) genes with their electrophysiological properties. Thus, the relationship between gene expression and cellular/behavioral phenotypes is complex, and this complexity must be taken into account in future studies into the ion channel mechanisms mediating hypoexcitability of PVIs in Arx CKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for single cell RT-qPCR and clustering and validation of these techniques have been previously described (Adelman et al, 2019). Briefly, the RNA collected from each cell was reverse transcribed and amplified using T7 linear amplification (Epicentre, MessageBOOSTER kit for cell lysate), cleaned with RNA Cleaner & Concentrator-5 columns (Zymo Research), and assessed using qPCR with optimized primers and SsoAdvanced SYBR Green Master Mix (BIO-RAD).…”
Section: Single Cell Amplification and Qpcrmentioning
confidence: 99%
“…To classify afferent subtypes we used single-cell RT-qPCR to analyze transcripts of 28 genes previously used in a study for classification of identified cutaneous afferents (Adelman et al, 2019). These genes were shown to identify clusters that largely replicated the clusters produced by bulk, single cell RNAseq of DRG neurons unidentified with respect to innervation target or functional phenotype (Usoskin et al, 2015;Zeisel et al, 2018).…”
Section: Automated Hierarchical Clustering (Ahc) Based On Mrna Expression and Afferent Location Reveal Distinct Neuronal Clustersmentioning
confidence: 99%
“…Throughout development distinct neurotrophic factors regulate neuronal subtype formation and innervation; however, these signaling growth factors also display non-canonical roles (Moqrich et al, 2004) (Shelton and Reichardt, 1984) (Mendell, 1996). Recent investigations also demonstrate that developing sensory neurons display changing transcriptional identities and functional maturation from the neonatal period through adulthood (Sharma et al, 2020) (Jankowski et al, 2014) (Adelman et al, 2019). While growth factors clearly alter subtype survival, we detect that modulation of neuronal GH signaling results in functional changes to normal somatosensory processing in both the skin (Ford et al, 2019) and the muscle.…”
Section: Discussionmentioning
confidence: 47%